Pengembangan LKPD Berbasis Liveworksheet Pada Materi Bangun Datar Siswa Kelas IV SD - Laily Maghfiroh; Jayanti Jayanti; Ida Suryani (Journal on Education, 2023)
Material for grade IV elementary school students that is valid, practical and has potential effects. The research method used in this research is Research and Development. This development process uses the ADDIE model Steps. The data collection techniques used were questionnaires, interviews, observation and documentation, with the results obtained by 82% of media experts, 95% of material experts and 97% of linguists so that the Liveworksheet-based LKPD is categorized as very valid with revisions. Teacher response questionnaires get 96%, student questionnaires in one to one amount to 95.55% while small groups get a percentage of 95.83% if it is concluded then get 95.79% So that the Liveworksheet-Based LKPD is categorized as practical. Field trials get 9.10 so that the Liveworksheet-based LKPD has the potential effect of being used in learning. Thus the Liveworksheet-based LKPD is very suitable to be used as a learning medium for class IV SD.